Pengaruh Bauran Pemasaran Terhadap Keputusan Berkunjung Wisatawan Di Lawangwangi Creative Space- Dago Giri Bandung - Titing Kartika; Nurull Rochmah Pramadika; Apay Safari (Jurnal Sains Terapan Pariwisata, 2016)
The tourism industry development cannot be separated from the marketing mix. The marketing mix is an attempt to inform and to persuade customers to buy and to use certain products or services as well as a factor that can influence to consumer’s decision; one of them is decision to visit a tourist attraction. Marketing is not done aggressively and comprehensively through social media account or website. Likewise some individual target mark it’s that found by the authors are not to aware of tourism products that offered by Lawangwangi Creative Space. This study aimed to apply the marketing mix in Lawangwangi Creative Space; the decision of tourist to visit Lawangwangi Creative Space as well as the influence of marketing mix for the decision of tourist to visit to Lawangwangi Creative Space. This study uses a simple linear regression equation where the regression coefficient (b) obtained for the decision to visit is at 3,214 and it has positive mark, which means each happened an increase 1 point in the marketing mix, predicated the decision been able to increase by 3,124 units. The value of the constant (a) of 1,858 which indicates the value of decision of tourists to visit Lawangwangi Creative Space does not do the marketing mix. The results from this research shows that the marketing mix contributed for 52.3% of thetourists visiting the decisiontoLawangwangi Creative Space, while 47.7% is a large contribution from the influence of other variables that not examined.